The Stream of Behavior: Explorations of Its Structure &Amp; Content.
DOI: 10.1037/11177-012
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Spontaneous Talk.

Abstract: THE EDITOR FINDS The Study of Spontaneous Talk a fascinating experience. How infrequently does the opportunity arise to witness from almost the very beginning the exploration of a true scientific terra incognita! And when this unknown is so familiar in a fragmentary and intensely personal way, the fascination is surely enhanced. The authors describe their data as "at once rare and complicated," and comment that this "precluded the formulation of hypotheses at the outset." They liken their problem to that of "g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…A large body of research, however, indicates that men talk more than women do (Argyle et al, 1968;Bernard, 1972;Hilpert et al, 1975;Kester, cited in Kramer, 1974;Marlatt, 1970;Rosenfeld, 1966;Soskin and John, 1963;Strodtbeck, 1951;Swacker, 1975).…”
Section: Conversational Division Of Labormentioning
confidence: 99%
“…A large body of research, however, indicates that men talk more than women do (Argyle et al, 1968;Bernard, 1972;Hilpert et al, 1975;Kester, cited in Kramer, 1974;Marlatt, 1970;Rosenfeld, 1966;Soskin and John, 1963;Strodtbeck, 1951;Swacker, 1975).…”
Section: Conversational Division Of Labormentioning
confidence: 99%
“…(SUMMER 1975) has as yet been no adequately controlled test of this assumption. Soskin and John (1963) and Purcell and Brady (1965) noted that their subjects' references to being observed disappeared after one or two days. These findings only suggest rapid adaptation, however, and do not prove either adaptation or the lack of reactive effects.…”
mentioning
confidence: 99%
“…In this constricted private setting, the intrusive effects of a live observer are especially apparent. For these reasons, several investigators have pioneered development of mechanical recording devices for obtaining naturalistic behavioral data (e.g., Bernal, Gibson, William, and Pesses, 1971;Hoshiko and Holloway, 1968;Nordquist, 1971;Purcell and Brady, 1965;Soskin and John, 1963 server present. In short, this study compared the behavior of children and parents at home as recorded by audiotape recordings in two conditions: with an observer present and with the observer absent.…”
mentioning
confidence: 99%
“…An analysis of the products revealed that the nonsocial coding condition produced more low frequency (unusual) words than the social condition. Soskin and John (1963) analyzed a series of ordinary adult conversations. Their data suggested that private speech is a rare or useless category of adult speech.…”
Section: Studies Of Communication Skills In Adultsmentioning
confidence: 99%